Teoria i polityka cen a ekonomika jakości - Wilczyński, Wacław (Wydział Prawa i Administracji UAM, 1973)
Up to now theory and price policy in Poland has not taken sufficiently into account criteria and motives of socialist economy. While the purpose of socialist economy is maximization of social utility effect in relation to inputs, prices are ruled by the so called cost principle and therefore they are not related to the quality and use value of the goods, particularly in the field of sales between enterprises, Thus it is necessary to employ achievements of quality economics for revising cost prices so that they might perform their parametric function. In the sphere of production works on economic optimization of quality are needed which is, however, dependent on changes in the functioning system of national economy and on increasing market equilibrium. The article also suggests that quality should be used for pricing two comparable products.
Theory Price Policy and Quality Economics